1984
DOI: 10.1159/000132061
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetics of Atlantic eels: C- and G-banding, nucleolus organizer regions, and DNA content

Abstract: C- and G-banding, silver staining, and cytofluorometric analysis of DNA content were carried out on two species of eels, Anguilla anguilla and A. rostrata, to compare them, to investigate the existence of sex chromosomes in both species, on which different authors disagree, and to understand the significance of the sex-independent variability found in one chromosome pair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 9 publications
3
43
0
Order By: Relevance
“…Wiberg, 1983;Sola et al, 1984;Viñas et al, 1996). Regional chromosomal duplications, produced either by DNA polymerase slippage or unequal crossing over (Warburton and Henderson, 1979;Jhanwar et al, 1981), could lead to the observed structural polymorphism.…”
Section: Resultsmentioning
confidence: 99%
“…Wiberg, 1983;Sola et al, 1984;Viñas et al, 1996). Regional chromosomal duplications, produced either by DNA polymerase slippage or unequal crossing over (Warburton and Henderson, 1979;Jhanwar et al, 1981), could lead to the observed structural polymorphism.…”
Section: Resultsmentioning
confidence: 99%
“…G-banding was very useful because it allowed some homologous chromosomes to be characterized; others pairs, however, showed very similar banding patterns. The fact that among the Anguilliformes studied A. anguilla (Wiberg, 1983), A. rostrata (Sola et al, 1984) and C. conger showed identifiable G-bands, while Muraena Murena helena (Cau et al, 1992) did not, increased the number of taxonomic affinities between Anguillidae and Congridae.…”
Section: Discussionmentioning
confidence: 97%
“…Clear G-bands were published for A. anguilla (Wiberg, 1983), A. rostrata (Sola et al, 1984) and more recently for some North American cyprinids (Gold et al, 1990;Gold & Li, 1991). Chiarelli et al, 1969Passakas, 1981So\iet al, 1980Park & Grimm, 1981Wiberg, 1983Ohno et al, 1973Solaef al, 1980Park & Grimm, 1981Passakas, 1981Nishikawa et al, 1971Solaef al, 1980Nishikawa et al, 1971Park & Kang, 1979Subrahmanyah & Ramamoorthi, 1971Park & Kang, 1979Ojima & Ueda, 1982Takai & Ojima, 1985Takai & Ojima, 1985Takai et al, 1987Nogusa, I960 Cau et al, 1988Takai & Ojima, 1985Deiana et al, 1990Takai & Ojima, 1985«/., 1991Ojima, 1985Ojima, 1985Nogusa, I960 Ojima, 1985Nishikawa & Sakamoto, 1977Thodeetal, 1985Murofushi etal, 1984 -data not reported NOR chromosomal patterns in Anguilliformes have been studied on only six species from different families, all of which presented a single pair of NOR chromosomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations